2013
DOI: 10.7567/jjap.52.03ba01
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Amorphous In–Ga–Zn–O Films Deposited at Different Sputtering Pressures

Abstract: The physical properties of amorphous In–Ga–Zn–O (a-IGZO) films deposited by DC sputtering under various sputtering pressures were investigated. The sputtering pressure was found to influence various physical properties. Lower sputtering pressures resulted in film densification and decreased both surface roughness and hydrogen concentration. In addition, transistor performance characteristics such as saturation mobility and sub-threshold swing improved as the sputtering pressure decreased. These results yield i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In addition, the S-value of 0.21 V/ decade and Ion/off ratio of 2.63×10 10 were also obviously improved for the device deposited under 1 mTorr. As reported in previous papers [8,9], a significant improvement in device performance was observed for the TFTs utilizing a-IGZO channel deposited at a low pressure of 1 mTorr. They determined the reason for this improvement by physical analysis variation, wherein film density and roughness of the a-IGZO films deposited at different chamber pressures were evaluated.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the S-value of 0.21 V/ decade and Ion/off ratio of 2.63×10 10 were also obviously improved for the device deposited under 1 mTorr. As reported in previous papers [8,9], a significant improvement in device performance was observed for the TFTs utilizing a-IGZO channel deposited at a low pressure of 1 mTorr. They determined the reason for this improvement by physical analysis variation, wherein film density and roughness of the a-IGZO films deposited at different chamber pressures were evaluated.…”
Section: Methodssupporting
confidence: 78%
“…This improvement could be attributed to densification of the a-IGZO film, however information addressing how the densification of the a-IGZO film improved the electrical properties is lacking. Yasuno et al [9] also reported that densification and roughness can be improved at a lower sputtering pressure, which also resulted in improvement saturation mobility (μ sat ) and sub-threshold swing (S.S.). However, there is still a lack of direct electronic structure evidence to support the variation electrical properties.…”
Section: Introductionmentioning
confidence: 97%
“…Yasuno et al . 64 and Trinh et al . 65 observed that electrical properties of the film depend on surface roughness and porosity of film.…”
Section: Resultsmentioning
confidence: 94%
“…The microwave photoconductivity decay (µ‐PCD) method is known as a nondestructive and contactless technique used for direct evaluation of various semiconductors. [ 24–26 ] It enables characterization of the recombination and trapping processes of photogenerated carriers by observing the microwave reflectivity. Therefore, the peak reflectivity signals of the photoconductivity are correlated with the quality (i.e., the defects) of the film that affects device performance.…”
Section: Resultsmentioning
confidence: 99%